Meningkatkan Self Efficacy Pelajaran Matematika melalui Layanan Penguasaan Konten Teknik Modeling Simbolik - Sadewi, Aulia Ika; Sugiharto, DYP; Nusantoro, Eko (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
The purpose of this research is to improve the self-efficacy toward mathematics through mastery of content services with symbolic modeling techniques. This type of research is experimental research. The design uses Pre Experimental Design with experimental pattern One Group Pre Test and Post Test Design. The research sample was selected using purposive sampling technique as many as 28 student.The metods of data collection using self-efficacy scale for mathematics. While the analysis of the data using descriptive analysis techniques and quantitative data analysis. From the results of hypothesis testing showed thitung = 12.29 and ttabel = 2.005, so thitung > ttabel. These results indicate that there are significant differences between self-efficacy toward mathematics in class VIII in SMP Negeri 1 Lasem before and after a given service with content mastery of symbolic modeling techniques. The conclusions of this study are self-efficacy toward mathematics can be improved through mastery of content services with symbolic modeling techniques